Single-Cell RNA Sequencing Reveals the Interaction of Injected ADSCs with Lung-Originated Cells in Mouse Pulmonary Fibrosis - Mamatali Rahman; Zhao-Yan Wang; Jun-Xiang Li; Hao-Wei Xu; Rui Wang; Qiong Wu (Stem Cells International)
Pulmonary fibrosis (PF) is a severe chronic lung disease with little effective treatment options other than lung transplantation. Adipose-derived mesenchymal stem cells (ADSCs) have been shown to exert therapeutic effects on PF, but the underlying mechanisms remain to be further elucidated. Here, we show the interaction of ADSCs and lung-originated cells at the single-cell level, using bleomycin- (BLM-) induced mice PF model and green fluorescent protein– (GFP–) labeled mouse ADSCs. The intratracheally injected ADSCs were successfully recollected with flow cytometry and, together with lung-originated cells, were subjected to single-cell RNA sequencing (scRNA-seq). The ADSC treatment drastically changed the transcriptomic profile and composition of lung cells, especially macrophages. We explored the signal pathway interactions between ADSCs and lung-originated cells, showing potentially regulative pathways including NGR, ANNEXIN, HGF, and PERIOSTIN. Our data indicate that the injected ADSCs increased the number of Trem2+ antiinflammatory lung macrophages and lowered further inflammation and fibrosis in the lung. Our work realized the direct analysis of injected ADSCs to explore its in vivo interaction with the lung environment under PF and may provide critical information for future engineering of ADSCs to achieve better therapeutic effects in PF.